X-Ray-Controlled Generation of Peroxynitrite Based on Nanosized LiLuF4 :Ce3+ Scintillators and their Applications for Radiosensitization - Du, Zhen (Advanced materials (Deerfield Beach, Fla.), 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.